2014
DOI: 10.1111/ijn.12297
|View full text |Cite
|
Sign up to set email alerts
|

Nurse competence between three generational nurse cohorts: A cross‐sectional study

Abstract: Research indicates significant differences between nurse cohorts in many work-related factors. This study compared nurse competence between three generational cohorts comprising the current nursing workforce. The Nurse Competence Scale was used to collect data for this cross-sectional study from 2052 nurses in a university hospital in Finland. Data were analysed statistically. Significant differences were found between nurse cohorts in their competence. The length of work experience had a significant impact on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 24 publications
6
76
3
Order By: Relevance
“…Nurses reporting higher competence also reported a higher frequency of using competence in twelve studies (Meretoja , Meretoja & Leino‐Kilpi , Meretoja et al . ,b, , Cowin et al . , , Mäkipeura et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses reporting higher competence also reported a higher frequency of using competence in twelve studies (Meretoja , Meretoja & Leino‐Kilpi , Meretoja et al . ,b, , Cowin et al . , , Mäkipeura et al .…”
Section: Resultsmentioning
confidence: 99%
“…Sociodemographic variables, such as older age in eight studies (Meretoja , Meretoja et al . ,b, , Salonen et al . , Stobinski , Hamström et al .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the majority of studies on nursing competence remain descriptive in nature, and do not go beyond identifying the antecedents of competence. Indeed, many of the existing studies have aimed at identifying the attributes of nursing competence (Axley, 2008;Smith, 2012;Valloze, 2009), the scales to measure it (Bartlett et al, 2000;Cowan et al, 2008;Liu et al, 2009;Meretoja et al, 2004a), and the level of competence demonstrated by nurses (Chang et al, 2012;Meretoja and Leino-Kilpi, 2003;Meretoja et al, 2014). Only a limited number of studies have explored the antecedents of competence, such as critical thinking ability (Chang et al, 2011;Wangensteen et al, 2012), but none of them have explored the impact of learning.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses with a longer length of work experience scored higher in competence than younger professionals, showing the need for specific interventions in the training of different generations of nurses to ensure the maintenance of competence and high-quality care to the patient (15) .…”
Section: Discussionmentioning
confidence: 99%